Предмет: Алгебра,
автор: matieva2002
Упростите выражение: √60+(√3-√5)²
Ответы
Автор ответа:
0
√60+(√3-√5)²
√60 + ( √3)^2 - 2*√3*√5 + (√5)^2 = √60 + 3 - 2√16 + 5 = √60 +8 -√4*15= √60 + 8 - √60 = 8
√60 + ( √3)^2 - 2*√3*√5 + (√5)^2 = √60 + 3 - 2√16 + 5 = √60 +8 -√4*15= √60 + 8 - √60 = 8
Автор ответа:
0
как у вас получлось - 2√16?
Автор ответа:
0
??
Автор ответа:
0
там корень 2√15=√60
Автор ответа:
0
просто человек описался
Похожие вопросы
Предмет: Математика,
автор: 147051
Предмет: История,
автор: Аноним
Предмет: Литература,
автор: vikacreative12
Предмет: Химия,
автор: butirina1207